The activity of mediation by notary in Rolandino’s Summa (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The essay investigates the mediation activity conducted by medieval notary between law, economy and society in testaments, in bequest for the repayment of usury (male ablata) and in training and writing contracts: the aim is enlighting the crucial role played by notary in medieval cities. The contribution shows by the study of Rolandino’s works and bibliography that the deep knowledge of this professional group is an essential tool for understanding society, economy and culture in medieval italian cities.
Keywords: Notary; Testament; Male ablata; Contracts; Rolandino Passeggeri